2010
DOI: 10.1007/s11064-010-0202-7
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Minocycline on Cuprizone Induced Cortical Demyelination

Abstract: In this study, we investigated the potential of minocycline to influence cuprizone induced demyelination in the grey and white matter. To induce demyelination C57BL/6 mice were fed with cuprizone for up to 6 weeks and were analysed at different timepoints (week 0, 4, 5, 6). Mice treated with minocycline had less demyelination of the cortex and corpus callosum compared with sham treated animals. In the cortex decreased numbers of activated and proliferating microglia were found after 6 weeks of cuprizone feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 43 publications
8
38
0
Order By: Relevance
“…Taken together with the observation that cuprizone-induced demyelination is attenuated by minocycline, which also reduced Ox42/CD11b-expressing microglia, these studies support the idea that the effects of cuprizone on oligodendroglia may be mediated at least in part through cytokine secretion by activated microglia [258]. In other studies, minocycline also showed beneficial effects in attenuating the myelin damage in both cortex and corpus callosum after 4–6 weeks of cuprizone [259]. When administered simultaneously with cuprizone, minocycline improved motor coordination in the beam walking test, although the differential protection of various myelin-specific proteins was partial and region-dependent.…”
Section: The Prodromal High-risk Phenotype and Onset Of Schizophreniasupporting
confidence: 72%
See 1 more Smart Citation
“…Taken together with the observation that cuprizone-induced demyelination is attenuated by minocycline, which also reduced Ox42/CD11b-expressing microglia, these studies support the idea that the effects of cuprizone on oligodendroglia may be mediated at least in part through cytokine secretion by activated microglia [258]. In other studies, minocycline also showed beneficial effects in attenuating the myelin damage in both cortex and corpus callosum after 4–6 weeks of cuprizone [259]. When administered simultaneously with cuprizone, minocycline improved motor coordination in the beam walking test, although the differential protection of various myelin-specific proteins was partial and region-dependent.…”
Section: The Prodromal High-risk Phenotype and Onset Of Schizophreniasupporting
confidence: 72%
“…Notably in this study, spontaneous re-expression of the myelin proteins PLP, MBP and 2′,3′-cyclic nucleotide 3′-phosphodiesterase was demonstrated in the corpus callosum without minocycline, but in the cortex, progressive damage by cuprizone continued. Minocycline also did not affect OPC numbers or the extent of astrogliosis [259], suggesting that direct protection of these cells by minocycline was less likely. Besides minocycline, modulation with antipsychotic drugs such as quetiapine and clozapine [260] has also shown enhanced protection or cellular repair in the demyelinated lesions using simultaneous treatment with cuprizone [260] or after cuprizone withdrawal [261].…”
Section: The Prodromal High-risk Phenotype and Onset Of Schizophreniamentioning
confidence: 99%
“…We assume that the increased activation of microglia/monocytes and/or astrocytes in the white compared to the gray matter results in a higher lesion expansion. In support of this assumption is the observation that in the cuprizone model, explicit microgliosis is evident in regions of profound demyelination [62], that prevention of demyelination is paralleled by a reduced activation of microglia cells [63][64][65], and that the application of the microglia inhibitor minocycline [66] ameliorates demyelination in the cuprizone model [67]. Similar observations have been reported in the LPC model [68].…”
Section: Discussionsupporting
confidence: 59%
“…62 Likewise, FLA in this study alleviated the astrocytes and microglia proliferation in CPZ-treated mice, in addition to ameliorating oligodendrocyte loss and myelin breakdown. The mechanism for this action of FLA may be related to its ability of cell cycle inhibition as discussed above.…”
Section: Flavopiridol Alleviated Cpz-induced Activation Of Astrocytessupporting
confidence: 50%